Population Administration Services in Makassar City, Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article analyzes and looks for implementation models of population administration service policies atthe Makassar City Population and Civil Registry Office. The indicators used in this study refer to the van Meter andvan Horn models using six indicators: policy standards and objectives; resource; inter-organizationalcommunication; characteristics of implementing agents; disposition of implementor; and economic, social andpolitical conditions. By using a qualitative approach, this study shows that the implementation of populationadministration services at the Makassar City Population and Civil Registry Service is still not well implemented.Lack of communication and socialization to the community is the cause of their not being able to carry out theirmain tasks and functions properly. This study recommends the coordination variable in policy implementation, inorder to measure the success or failure of the policy.